A NOTE ON THE ARROW’S IMPOSSIBILITY THEOREM - Jain, Ritesh (Economic Annals, 2015)
This paper generalizes Arrow’s impossibility theorem (Arrow1950) in two directions. First we allow agents to have incomplete preferences, and the admissible domain of preferences can be a proper subset of the full domain.